Praeacedes atomosella (Walker, 1863) and Phereoeca praecox Gozmány & Vári, 1973 - two case-bearing moths new to the Fauna of La Réunion (Lepidoptera: Tineidae). - Bippus, Maik (Contributions to Entomology = Beiträge zur Entomologie, 2016)
Two species of Tineidae, Praeacedes atomosella (Walker, 1863) and Phereoeca praecox Gozmány & Vári, 1973 are recorded new to the fauna of La Réunion. Their biology is explained; larvae, adults and genitalia are illustrated.KeywordsLepidoptera, Tineidae.